PERAN LEAFLET ASI EKSLUSIF TERHADAP PENGETAHUAN IBU TENTANG ASI EKSLUSIF DAN MOTIVASI UNTUK MENYUSUI SECARA EKSLUSIF DI BPS NY. DJUWEDAH KEBASEN KABUPATEN BANYUMAS - Muslikha, purniati; Purwanti, Sugi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
The decrease knowledge and motivation about the important of exclusive breastfeeding will impact to the scope application of exclusive breastfeeding until be needed healthy promotion than can motivated mother for give suck in a exclusive manner requirement like utilize leaflet as information media for upgrade motivation and knowledge. To find out of exclusive breastfeeding for the mothers knowledge about exclusive breastfeeding and motivation for give suck in a exclusive manner. Kinds of research pre-experiment with research design the one group pretest and post test design. The population of this knowladge is the whole pregnant mother which pay a visit at BPS Mrs. Djuwedah Kebasen Subdistric Banyumas Regency 2010. The sample number take over 31 persons. Data analysis utilized frequency distribution and Wilcoxon test. 1) Before accept the leaflet a big part respondent precisely knowledge is 17 persons (54,8%), after accepting leaflet a big part pricisely knowledge is 15 persons (48,4%), 2) before accept the a big part has medium motivation that is a big as 20 persons (64,5%), after accepting leaflet a big part has high motivation for give suck in a exclusive manner that is as many as 16 persons (51,6%), 3) the result of statistic analysis be obtained p-value for knowledge 0,000 < 0,001 and motivation 0,000< 0,001, so Ho was refuse. The leaflet exclusive breastfeeding have a role the upgrading of mother knowledge about exclusive breastfeeding and mother motivation for give suck in a exclusive manner. Better the health staff utilize leaflet as information media wiht in carry an extension because the leaflet exclusive breastfeeding have a role show in increase mothers knowledge give suck about exclusive breastfeeding and mothers motivation for give suck in a exclusive manner. Keyword: Knowledge, motivation and leaflet exclusive breastfeeding.